INTEGRATION OF RELIGION AND SCIENCE IN ISLAMIC UNIVERSITIES - Ikfi Khoulita; Asep Rahmatullah; Sofwan Hadi (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2020)
AbstractThe Integration Project of Islam and Science in Indonesia in particular has gained momentum in the last ten years. Several Islamic higher education institutions have transformed themselves from STAIN/IAIN into UIN, a step that some consider scientific ijtihad in integrating science and Islam at Islamic universities. This step of status transfer was also accompanied by the growth of buildings that all looked like “Inpres Primary Schools” in remote areas, into magnificent and modern campuses. Physical development can be said to be successful, because the image of Islamic universities that have transformed into universities is not inferior to other universities, which have long been established and manage various scientific disciplines.